GENDER EDUCATION IN HADITH PERSPECTIVE: DEVELOPING EQUALITY IN FORMAL EDUCATION - Gusni; La Ode Ismail Ahmad; Muhammadiyah Amin; Abd. Bashir Fatmal (Jurnal Diskursus Islam, 2025)
This study examines gender education in the perspective of hadith as an effort to develop equality in formal education. The study aims to analyze the understanding of the concept of gender in hadith and its implications for formal education in Indonesia. Using a qualitative method with a content analysis approach, the study explores hadith-reports on gender, including the creation of women, conjugal responsibilities, women’s leadership, and partnership between men and women. The results show that the traditions provide an understanding that men and women are equal, albeit with different roles and responsibilities. The main obstacles in gender-related formal education are gender bias in learning materials and stereotyping of gender roles in the school environment. Islamic education plays an important role in removing these biases through contextualized and fair interpretation of hadith. In conclusion, the integration of moral values and gender education in the formal education system can create a more just and harmonious society. The implication is that collaboration between educators, policymakers and communities is needed to ensure gender equality in formal education.